Blocking the L-type Ca2+ channel (Cav 1.2) is the key mechanism for the vascular relaxing effect of Pterodon spp. and its isolated diterpene methyl-6α-acetoxy-7β-hydroxyvouacapan-17β-oate. (October 2015) - de Fátima Reis, Carolina; de Andrade, Daniela Medeiros Lobo; Neves, Bruno Junior; de Almeida Ribeiro Oliveira, Leandra; Pinho, José Felippe; da Silva, Leidiane Pinha; Cruz, Jader Dos Santos; Bara, Maria Teresa Freitas; Andrade, Carolina Horta; Rocha, Matheus Lavorenti
Graphical abstract: Abstract: Pterodon spp. Vogel (Fabaceae), popularly known as "sucupira", has ethnopharmacological application which is described as having antispasmodic and relaxant effects. Hence, it was hypothesized that sucupira oil-resin (SOR) could induce smooth muscle relaxation. So, this study investigated the mechanisms involved in the vasorelaxant effect of SOR and its isolated diterpene (methyl-6α-acetoxy-7β-hydroxyvouacapan-17β-oate). Vascular reactivity experiments were performed using rat aortic rings ( n = 5–8) with ( E +) or without endothelium ( E −) in an isolated bath organ. The SOR (0–56 μg/mL) relaxed phenylephrine ( E +: 86.7 ± 7.1%; E −: 92.3 ± 4.7%) and KCl contracted rings ( E −: 97.1 ± 2.8%). In the same way, diterpene (0–48μg/mL) also relaxed phenylephrine ( E +: 94.5 ± 3.6%; E −: 92.2 ± 3.4%) and KCl contracted rings ( E −: 99.7 ± 0.2%). The pre-incubation of arterial rings with cyclopiazonic acid (reticular Ca 2+ -ATPase inhibitor), tetraethylammonium (K+ channels blocker) or MDL-12, 330A (adenylyl cyclesinhibitor) did not modify either SOR- or diterpeneinduced vasorelaxation. However, ODQ (guanylyl cyclase inhibitor) impaired only diterpene-induced vasorelaxation. SOR and diterpene significantly reduced CaCl2 -induced contraction stimulated by Bay K8644 (1 μM), phenylephrine (0.1 μM) or KCl solution (40 mM). Computational molecular docking studies demonstrated that the vasodilator effect of diterpene relies on blocking the Cav 1.2 channel, and patch clamp results showed that diterpene substantially decreased the ionic current through Cav 1.2 in freshly dissociated vascular smooth muscle cells. These findings suggest that SOR and its isolated diterpene induce endothelium-independent vascular relaxation by blocking the L-type Ca 2+ channel (Cav 1.2).